A giant liver hydatid cyst: a case report and review of the literature - Ahmad Izadpanah; Alimohamamad Bananzadeh; Gholamreza Abdollahifard; Cambyz Irajie; Qasem Asgari; Elham Ahmadi; Mohammad Javad Yavari Barhaghtalab (Iranian Journal of Colorectal Research, 2024)
Background: Cystic echinococcosis (CE) is a parasitic disease caused by the larval stages of taeniid cestodes of the genus Echinococcus which is considered a neglected disease of public health worldwide. CE primarily affects the liver and demonstrates distinctive radiological findings in computed tomography and ultrasonography. Surgery is considered the mainstay of CE treatment. Case presentation: The patient was a 17-year-old man who was admitted to the Emergency Department of Shahid Faghihi Hospital affiliated with the Shiraz University of Medical Science with dull right upper quadrant abdominal pain, loss of appetite, abdominal distention, and fullness. Abdominal computed tomography (CT) scan revealed a giant hepatic cyst measuring about 24 × 20 × 15 cm in the RHL with a pressure effect on the right kidney, pancreas, and bowel loops and another smaller one measuring 9× 8 × 8 cm in the left liver lobe. Semi-chevron incision was done and the patient underwent partial precystectomy with capitonnage and omentoplasty. Our case was the 5th rank according to the size of the recorded published cases in the literature.Conclusion: When dealing with a huge liver cyst, a high index of suspicion for echinococcal etiology becomes important in endemic areas like Iran. The choice of treatment for giant hepatic cysts substantially seems to be radical surgery by surgical ablation in general to mitigate the mortality and morbidity rate, because they are at risk of rupture, anaphylaxis, and so forth.